The politics of the Olympics: The case of the Sochi 2014 winter games - Karasaç, Ayşe. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This study aims to analyze the political aspects of the Sochi 2014 Winter Olympics that were held in the Russian Federation after many protests and controversies. The analysis of the Sochi case contributes to our understanding of the politics of the Olympics, the domestic politics of the host state, interstate contestations as well as continuities and changes in the modern Olympics and the Russian Federation. This thesis addresses the question of “Can the Sochi 2014 Winter Olympics be considered politically a distinct case in the Olympics?”. It examines the Sochi Olympics through online news, non-governmental organization reports and opinion polls, and also tries to scrutinize Russia’s Olympic experience by looking at other Olympic host states’ experiences with the contribution of the news, reports and the academic literature on Olympic history. Particularly leading to the LGBT rights’ taking place in the Olympic Charter and host city contract, an ethnic group’s anti-Olympic campaign’s being cause celebre, new security dynamics were peculiar to the Sochi Olympics. Since commonalities in the Olympics such as politicization, experiences of Olympic constructions and legacies predominated, the Sochi Winter Olympics cannot be politically put into a distinct place in the Olympics but the achievements of group protests show the changing dynamics of politicization in the Olympics.
Keywords: Olympics -- Political aspects.